Variability And Character Association Of Reproductive Traits In Exotic Rice Germplasm - Akhter, T; Ivy, NA; Rasul, MG; Mian, MAK (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Fifty two genotypes were evaluated to find out the genetic variability, character association, and path coefficient for reproductive traits of exotic rice germplasm in experimental field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur during December 2008 to May 2009. The analysis of variance showed significant variation for all the characters indicating wide genetic variability among the genotypes. The highest genotypic variance and phenotypic variance were found for pollen sterility and filled grains per panicle. High heritability and genetic advance were recorded for pollen sterility. Filled grains per panicle, days to 50% flowering, and pollen sterility of different genotypes had a high degree of significant positive association with grain yield per hill. On the basis of genetic parameters, associations and path analysis 52 genotypes might be selected considering the filled grains per panicle only. Key words: Variability; correlation coefficient; path coefficient; exotic rice DOI: http://dx.doi.org/10.3329/bjpbg.v23i1.9316 BJPBG 2010; 23(1): 39-44